Spin parity measurement of centrally produced (pi(+) pi(-)) in proton-proton collisions at 800 GeV/c - Markianos, Kyriacos (ScholarWorks@UMass Amherst, 1998)
Experiment E690 at Fermilab recorded 5.5 billion $p + p → p + X$ events using an 800 GeV/c proton beam and a liquid hydrogen target, during the 1991 fixed target run. We use a 0.5 billion subset of this sample, to study the reaction $p + p → p\sb{s}(π\sp+π\sp-)p\sb{f}$ for dipion invariant mass between threshold and 2.3 GeV/c$\sp2.$ We perform a partial wave analysis for dipion invariant mass between threshold and 1.5 GeV/c$\sp2.$ The assumption of S-wave dominance near threshold is sufficient to determine a single, continuous solution throughout the considered mass spectrum. Precision measurement of the production amplitude aids the mapping the low lying meson spectrum. Other possible studies using this data sample and analysis technique are: (1) the extension of the amplitude analysis above the 1.5 GeV/c$\sp2$ mass region using a the full event sample, and (2) the study of the produced amplitudes as a function of the relative angle between the two proton planes.